Investigation of Endohelminths in Some Fish Species Caught in the Dicle River and Keban Dam Lake - Doğan, Sibel; Dörücü, Mustafa (Durmuş Ali ARSLAN, 2024)
In this study, a total of 94 fish were used, including 10 Acanthobrama marmid, 17 Capoeta trutta, and 20 Capoeta umbla specimens, obtained from fishermen in the Dicle River and Keban Dam Lake in October 2021. It was found that 85 of the fish examined were infected. Diplostomum spathaceum was identified in the eye fluid, and Neoechynorhynchus rutili was identified in the intestines of the fish. A total of 2.846 parasites were found in the Dicle River, with 2109 D. spathaceum and 737 N. rutili, and the density, abundance, and prevalence of parasites were determined to be 66.18, 60.55, and 91.48, respectively. In Keban Dam Lake, a total of 2.846 parasites were detected, including 1.817 D. spathaceum and 737 N. rutili, and the density, abundance, and prevalence of the parasites were determined to be 54.80, 48.97, and 89.36, respectively.

Bu çalışmada, Ekim 2021 yılında Dicle Nehri’nden ve Keban Baraj Gölü’nden balıkçılardan alınan 10’ar adet Acanthobrama marmid, 17’şer adet Capoeta trutta, 20’şer adet Capoeta umbla olmak üzere toplam 94 adet balık kullanıldı. İncelenen balıkların 85 tanesinin enfekte olduğu belirlendi. Balıkların göz sıvısında Diplostomum spathaceum ve bağırsaklarında Neoechynorhynchus rutili teşhis edildi. Dicle Nehri’nde 2109 adet D. spathaceum, 737 adet N. rutili olmak üzere toplam 2846 adet parazit bulunmuş olup parazitlerin yoğunluk, bolluk ve yaygınlıkları sırasıyla 66,18, 60,55 ve 91,48 olarak saptandı. Keban Baraj Gölü’nde ise 1817 adet D. spathaceum, 737 adet N. rutili olmak üzere toplam 2846 adet parazit teşhis edilmiş olup parazitlerin yoğunluk, bolluk ve yaygınlıkları sırasıyla 54,80, 48,97 ve 89,36 olarak belirlendi.
Dicle Nehri ve Keban Baraj Gölü’nden Avlanan Bazı Balıklarda Endohelmintlerin Araştırılması
Keywords: Aquaculture and Fisheries (Other); Sucul Kültür ve Balıkçılık (Diğer)